Promotion of peace and peace education through schooling: Perspectives and experiences of girls and boys in Mauritius - Baligadoo, Priya Darshini (2018)
This thesis explores young boys’ and girls’ perceptions and experiences of their schooling in the small island developing state of Mauritius. It brings to the forefront problems related to cultural and structural violence that can hamper a peaceful schooling in three state secondary schools: a single-sex girls’ school, a single-sex boys’ school and a mixed school which also promote the educational theories of M.K. Gandhi and Rabindranath Tagore. The findings reveal that there can be a ‘fideistic’ attitude to Gandhi and Tagore in this context, which highlight the need for a critical peace education that question taken-for-granted assumptions. It also shows that in schools, problems can be hidden and not discussed.